Neurotravel - Muhammad Bunyau, Nur Ellyvia Lengidang; Nawin, Allanis Brooklyn; Romel Shaadat Khan, Anis Nadhirah; Gatu, Alvin (Universiti Teknologi MARA, Perak, 2023)
Neurodivergent travel signifies the experiences of neurodivergent individuals, whose neurological disorders and cognitive functioning are different from the normal norm. Traditional travel can be troubling for neurodivergent people for reasons such as sensory overload and unfamiliar environments. Plus, traditional travelling methods include searching the internet separately for information on how to handle neurodivergent episodes like panic attacks and anxiety attacks and spend less time arranging the itinerary while looking for accessible facilities for neurodivergent travellers. The goal of neurodivergent travel is to develop equitable and accessible travel that meet the various needs of neurodivergent travellers. NeuroTravel is an application for a resolution created to be used by neurodivergent travellers to make their travelling experience smoother and travelling feels much more accessible for them. It also comes with the objective to raise awareness about neurodivergent in general and neurodivergent travel. On the other hand, it includes the visited destination's details, and media integration as calming and distraction features. Plus, it can be an advantage for the neurodivergent traveller’s companion whereby the companion can give assistance to the traveller using tips and guides provided in the application. NeuroTravel also allows a patient-doctor communication in a chatbox feature to ease the communication between the travellers and their personal doctors. In contrast to neurodivergent travellers, various physical disabilities facilities have been created and are easily accessible. Thus, NeuroTravel application aims to be an application that is user-friendly for the travellers, and makes travelling easier and more comfortable for them. In order to reach potential users, the application will be commercialised through typically largely used platforms such as TikTok, Instagram and Facebook.